The Effect of Observational Education About Stroke on Family Function in Preventing Recurrent Stroke: observational education, stroke, family function - Dewi Wulandari; Ixora Ixora; Awan Hariyanto; Edi Yuswantoro (Jurnal Keperawatan Terapan, 2024)
Stroke is one of the causes of death and disability in both urban and rural areas. Stroke is caused by reduced blood flow to the brain which lasts for several seconds to several minutes, where if it occurs for more than a few minutes an infarction will occur in the brain tissue. The aim of the research is to determine the effect of observational education about stroke on family function in preventing recurrent strokes in family members who suffer from stroke. The research was carried out in the Baruharjo Community Health Center Work Area. Quasy Experimental research design with control group pretest-posttest design. The independent variable is Observational stroke education while the dependent variable is family function. The research population was all families of stroke patients in the Baruharjo Community Health Center Working Area. The sampling technique uses purposive sampling with a sample of 30 people. Data were analyzed using the Wilcoxon test. The research results showed that before observational education about stroke was carried out, the majority (17 respondents or 56.7%) had family function in preventing recurrent stroke in the sufficient category. Meanwhile, after observational education about stroke was carried out, almost all respondents (29 respondents or 96.7%) had the family function in preventing recurrent strokes in family members who suffered stroke in the good category. The results of quantitative data analysis using the Wilcoxon signed ranks test using the SPSS program showed that the statistical test results had a p value of <0.000 which was smaller than the value of p= 0.05. The family plays a very important role during the post-acute stage of care for stroke patients in hospital to meet daily care and rehabilitation needs. Caring for patients with stroke is a serious matter. Families, whatever their age and circumstances, need information, education and social support to be able to carry out patient care and be able to adapt to their new roles.